Rise of the titans: baleen whales became giants earlier than thought. (31st May 2019) - Bianucci, Giovanni; Marx, Felix G.; Collareta, Alberto; Di Stefano, Agata; Landini, Walter; Morigi, Caterina; Varola, Angelo
Abstract : Baleen whales (Mysticeti) are major ecosystem engineers, thanks to their enormous size and bulk filter feeding strategy. Their signature gigantism is thought to be a relatively recent phenomenon, resulting from a Plio-Pleistocene mode shift in their body size evolution. Here, we report the largest whale fossil ever described: an Early Pleistocene (1.5–1.25 Ma) blue whale from Italy with an estimated body length of up to 26 m. Macroevolutionary modelling taking into account this specimen, as well as additional material from the Miocene of Peru, reveals that the proposed mode shift occurred either somewhat earlier, or perhaps not at all. Large-sized mysticetes comparable to most extant species have existed since at least the Late Miocene, suggesting a long-term impact on global marine ecosystems.